The repair of melphalan-induced DNA adducts in the transcribed strand of active genes is subject to a strong polarity effect - Episkopou, H.; Kyrtopoulos, S.A.; Sfikakis, P.P.; Dimopoulos, M.A.; Souliotis, V.L. (Mutation Research - Fundamental and Molecular Mechanisms of Mutagenesis, 2011)
To investigate the mechanisms of the therapeutic action and drug resistance to the nitrogen mustard melphalan, melphalan-induced DNA damage repair and chromatin structure were examined along the p53, N-ras and d-globin gene loci in cells carrying different repair activities. In nucleotide excision repair-deficient XP-A cells, similar levels of adducts were found in all fragments examined, indicating uniform distribution of DNA damage. In both, repair-proficient CS-B and XP-C cells, faster repair was observed in regions inside the transcribed N-ras and p53 genes, compared to regions on both sides outside of the genes, while no such difference was observed for the inactive d-globin gene. Moreover, very fast adduct repair on the transcribed strand of the active genes was seen immediately downstream of the transcription start site, together with a steeply decreasing gradient of repair efficiency along the gene towards the 3'-end. In all cells analyzed, the above variation in DNA repair efficiency was paralleled exactly by the variation in the degree of local chromatin condensation, more relaxed chromatin being associated with faster repair. Similar results were obtained using peripheral blood mononuclear cells from healthy volunteers, suggesting that the existence of a repair gradient along transcribed genes may be a universal phenomenon. In conclusion, these findings demonstrate that the repair of melphalan adducts in the transcribed strand of active genes is subject to a strong polarity effect arising from variations in the chromatin structure. © 2011 Elsevier B.V.
Keywords: Chromatin condensation; Melphalan adducts; Region-specific repair; Repair gradient